Oral Exegesis as Text: Study of Hamza Yusuf's Communication, Characteristics, and Contextuality Aspects - Riza, Zikri; Mansurnoor, Iik Arifin (STAIN Majene, 2025)
Oral practice can be principally viewed as text because it is classified as meaningful action. Often occurring in religious traditions, meaningful action can take the form of delivering oral exegesis both in everyday life and in the virtual world, as Hamza Yusuf did. Employing an interdisciplinary approach, namely communication, orality and contextuality, I attempt to analyze the phenomenon of the contemporary Quran. The result unveils that inquiry as a text appears to produce a clear construction of understanding. From a communication point of view, Yusuf's oral exegesis, especially the interpretation of QS. al-Hujura>t (49) verse 13, tries to convey the basic concepts of humanity which are really needed in the contemporary era prioritizing collective and behavioral ideas. Furthermore, Yusuf's practice of oral exegesis also fulfills all the characteristics of orality with interpretive contextual material that comes from the history of his life with intercultural communication nuance.",